2020
DOI: 10.1371/journal.pone.0243392
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of synthetic analogs of the naturally occurring quinolone alkaloid N-methyl-8-methoxyflindersin

Abstract: Leishmaniasis is a neglected, parasitic tropical disease caused by an intracellular protozoan from the genus Leishmania. Quinoline alkaloids, secondary metabolites found in plants from the Rutaceae family, have antiparasitic activity against Leishmania sp. N-methyl-8-methoxyflindersin (1), isolated from the leaves of Raputia heptaphylla and also known as 7-methoxy-2,2-dimethyl-2H,5H,6H-pyran[3,2-c]quinolin-5-one, shows antiparasitic activity against Leishmania promastigotes and amastigotes. This study used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Although animals treated with glucantime exhibited a significative decrease in lesion size and low parasitism, in the histopathology analysis, amastigote forms could be easily recognized, which, in turn, had a correlation with a significant inflammatory response, composed of macrophages with a low number of amastigote forms. Corroborating our results, a previous study showed that synthetic quinoline alkaloids were active in hamsters infected with L. (V.) panamensis and in histopathological studies, it was observed that there was a significant reduction in the inflammatory infiltrate in comparison with the non-treated animals [54], suggesting that the high leishmanicidal activity induced by quinolines leads to a reduction in the inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 90%
“…Although animals treated with glucantime exhibited a significative decrease in lesion size and low parasitism, in the histopathology analysis, amastigote forms could be easily recognized, which, in turn, had a correlation with a significant inflammatory response, composed of macrophages with a low number of amastigote forms. Corroborating our results, a previous study showed that synthetic quinoline alkaloids were active in hamsters infected with L. (V.) panamensis and in histopathological studies, it was observed that there was a significant reduction in the inflammatory infiltrate in comparison with the non-treated animals [54], suggesting that the high leishmanicidal activity induced by quinolines leads to a reduction in the inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 90%
“…Although they did not meet the SI ≥ 10 criteria, both showed a potent effect on L. (L.) amazonensis amastigotes. Súarez et al obtained similar results [41] working with synthetic analogs of quinolones and alkaloids (1,2,3,4-tetrahidro(benzo)-3-quinolin-ol and 2-amino-8-hidroxiquinoline), with SI~5.0. Indeed, the application of the SI criterion is controversial for in vitro tests used in drug research for infectious diseases [40].…”
Section: Cytotoxicity and Selectivity Index In Mammalian Cellsmentioning
confidence: 69%
“…Indeed, the application of the SI criterion is controversial for in vitro tests used in drug research for infectious diseases [ 40 ]. Once in in vivo tests, these compounds induced a total reduction of lesions and no cytotoxicity-related clinical effects [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, one could still assess that the effect promoted by the introduction of a methyl group is most accentuated that the one induced by a hydroxy group. By the end of 2020, Suarez et al used in silico techniques to identify synthetic quinoline alkaloids with a structure similar to the natural product N-methyl-8-methoxyflindersine and evaluated them against L. (V.) panamensis promastigotes and amastigotes [63]. The results demonstrated that, from the entire list of evaluated derivatives, only one (77, Figure 29) presents considerable levels of antileishmanial activity (IC 50 [promastigotes] = 10.0 ± 4.7 µM and IC 50 [amastigotes] = 6.6 ± 2.6 µM) and low levels of toxicity (SI = 5.5).…”
Section: Quinoline Derivatives As Antileishmanial Agents Post-2013mentioning
confidence: 99%